2013
DOI: 10.1002/mabi.201300329
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Separation of Conjugated Polymers Using a Water Soluble Glycoprotein Matrix: From Fluorescence Materials to Light Emitting Devices

Abstract: Optically active bio-composite blends of conjugated polymers or oligomers are fabricated by complexing them with bovine submaxilliary mucin (BSM) protein. The BSM matrix is exploited to host hydrophobic extended conjugated π-systems and to prevent undesirable aggregation and render such materials water soluble. This method allows tuning the emission color of solutions and films from the basic colors to the technologically challenging white emission. Furthermore, electrically driven light emitting biological de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…studies. 16,17,20 Thus, the R dye aggregates strongly in aqueous solutions which is manifested by its quenching [Fig. 2(A)], while no aggregates are observed in the complexed PGM solution [ Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…studies. 16,17,20 Thus, the R dye aggregates strongly in aqueous solutions which is manifested by its quenching [Fig. 2(A)], while no aggregates are observed in the complexed PGM solution [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 Since that, a conformational study on particular type may be generalized to the entire mucin family. 4 A member of this family, the Pig Gastric Mucin (PGM) is glycoprotein which belongs to the membrane and extracellular secreted proteins family with high molecular weight (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). PGM structure is comprised of many repeating building blocks which consist of rich glycosylated oligosaccharide chains that make up approximately 80% of PGM Mw that is arranged in 5-15 oligosaccharide's of fucose, galactose, Nacetylgalactosamine, Nacetylglucosamine, and mannose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we demonstrated a new paradigm facing the current WLED fabrication challenges. We suggested exploiting natures' ability to form many types of stable and controllable host–guest systems to reduce the unwanted nonradiative energy transfer mechanisms in dyes which are in close proximity.…”
Section: Introductionmentioning
confidence: 99%